Plant Hormones - Recent Advances, New Perspectives and Applications 2022
DOI: 10.5772/intechopen.102814
|View full text |Cite
|
Sign up to set email alerts
|

Role of Endogenous and Exogenous Hormones in Bioactive Compounds Production in Medicinal Plants via In Vitro Culture Technique

Abstract: The natural compounds produced in plants are classified into two major groups (Primary and secondary metabolic compounds). These compounds are the precursor materials for thecompounds of the second group, which are represented by secondary metabolites, most of which produce from three main compounds: shikimic acid, acetate, and fatty acids. Primary metabolites are the basic units in the metabolism of secondary compounds. Tissue cultures of plants are used to produce large quantities of secondary metabolic prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…ABA (abscisic acid) is a plant hormone formed from the breakdown of the carotenoid pigment violaxanthin, a 40-carbon molecule. The addition of growth hormones such as auxins and cytokinins can stimulate an increase in the production of secondary plant metabolites (Ibrahim, 2022). Wang et al (2018) stated that auxin is essential for average plant growth and development, especially concerning the ARF-Aux/IAA interaction.…”
Section: Resultsmentioning
confidence: 99%
“…ABA (abscisic acid) is a plant hormone formed from the breakdown of the carotenoid pigment violaxanthin, a 40-carbon molecule. The addition of growth hormones such as auxins and cytokinins can stimulate an increase in the production of secondary plant metabolites (Ibrahim, 2022). Wang et al (2018) stated that auxin is essential for average plant growth and development, especially concerning the ARF-Aux/IAA interaction.…”
Section: Resultsmentioning
confidence: 99%
“…Chrysanthemum cinerariaefolium were utilized. Quercetin has been used as an antiviral and anti-asthmatic agent [37][38][39], as shown in Figure 4. Phenols, terpenoids, isoprenoids, and flavonoids were created as secondary metabolites.…”
Section: Callus Culture and Secondary Metabolitesmentioning
confidence: 99%
“…Adding some stimuli to the cell system helps increase the biosynthesis of some cellular compounds that can attain dividing into biotic and abiotic stimuli depending on their nature. Some studies have indicated the possibility of inducing callus production of active substances, such as increasing the production of alkaloids, saturated alkanes, flavonoids, and esters in plant cells when using abiotic stress factors causing stress (Ibrahim, 2022;Ewhayid et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…An increase in the concentration of the type of sugar added to the nutrient medium beyond the specified amount constitutes stress in the tissue, and this, in turn, stimulates the production of some bioactive substances, accelerating the withdrawal process and the absorption of alkaloids metabolizing products. In addition to their contribution to constructing primary and secondary products involved in the structural pathways, they produce specific compounds in plants, which can be their estimation (Park et al, 2008;Ibrahim et al, 2022).…”
Section: Introductionmentioning
confidence: 99%